Ultrafast singlet fission in rigid azaarene dimers with negligible orbital overlap - Alagna, Nicolò; Pérez Lustres, José Luis; Roozbeh, Ashkan; Han, Jie; Hahn, Sebastian; Berger, Felix J.; Zaumseil, Jana; Dreuw, Andreas; Bunz, Uwe H. F.; Buckup, Tiago (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2020)
Singlet fission (SF) has the potential to boost solar energy conversion. Research has focused on designing new strategies to tune the electrochemistry, photophysics, and device architecture at the molecular level to improve the efficiency of SF sensitizers. These studies indicate that SF efficiency strongly depends on morphology, packing, and chemical structure. In this work, we use time-resolved spectroscopy to study intramolecular SF in three covalently linked azaarene dimers. Their rigid structure makes them promising model systems to investigate the effect of chemical modification on intramolecular SF without any potential contributions from geometrical factors. Our experimental results along with theoretical calculations show that SF occurs in all three dimers, confirming SF in perpendicularly oriented chromophores with negligible overlapping π-systems. Additionally, a complex branching mechanism is discovered for the evolution of the singlet (S0S1) and the correlated triplet pair 1(T1T1) states. Although chemical modification has only a minor effect on SF rate and generation of the correlated triplet pair, it plays a critical role in the evolution toward the formation of free triplets. Finally, comparison of deaerated and aerated solutions underpins the effect of oxygen in altering the 1(T1T1) dynamics by opening new decay pathways.
Gesehen am 17.11.2020